Otitis Media Supuratif Kronik Auris Dextra Tipe Aman Fase Aktif Pada Anak Usia 2 Tahun : Sebuah Laporan Kasus - Indah Kurnia Putri Waruwu; Mukhlis Imanto (CV. Jasa Sukses Abadi, 2026)
Benign-type chronic suppurative otitis media (CSOM) is a chronic middle ear infection characterized by a central tympanic membrane perforation and persistent otorrhea without cholesteatoma, with inflammation limited to the middle ear mucosa. Benign-type CSOM cases in children under 3 years of age are rarely reported, despite this age group having a high risk of recurrent ear infections due to the immature anatomy of the Eustachian tube, which is shorter, wider, and more horizontal compared to that of adults. We report a case of a 2-year-old boy who presented to the ENT Outpatient Clinic of Dr. H. Abdul Moeloek Regional General Hospital, Lampung Province, with a 2-month history of yellowish-white discharge from the right ear. The complaint was accompanied by hearing loss, indicated by the child not turning his head when called from behind. History-taking revealed six episodes of recurrent upper respiratory tract infection (URTI) within the past year, as well as exposure to cigarette smoke from the patient's father at home. Both conditions were significant risk factors contributing to the development of CSOM. Otoendoscopic examination revealed a subtotal central perforation of the pars tensa of the right tympanic membrane without cholesteatoma, establishing the diagnosis of active benign-type CSOM. The patient received aural toilet with 3% hydrogen peroxide for 3–5 days to clear the discharge, followed by topical ofloxacin 0.3% for 14 days. Parental education was provided regarding proper medication administration, keeping the ear dry, and avoiding cigarette smoke exposure. Accurate diagnosis and appropriate management are essential to prevent hearing impairment and delayed speech and language development in children.